Protocol for a single-arm confirmatory trial of adjuvant chemoradiation for patients with high-risk rectal submucosal invasive cancer after local resection: Japan Clinical Oncology Group Study JCOG1612 (RESCUE study) - Kohei Shitara; Yutaka Saito; Ryoji Kushima; Manabu Muto; Masaaki Ito; Tomohiro Kadota; Hiroaki Ikematsu; Takeshi Sasaki; Tomonori Mizutani; Gakuto Ogawa; Yoshinori Ito; Yukihide Kanemitsu (BMJ Open)
Introduction Intestinal resection with lymph node dissection is the current standard treatment for high-risk lower rectal submucosal invasive cancer after local resection; however, surgery affects patients’ quality of life due to stoma placement or impaired anal sphincter function. A recent study demonstrated that adjuvant chemoradiation yields promising results.Methods and analysis This study aims to confirm the non-inferiority of adjuvant chemoradiation, consisting of capecitabine and concurrent radiotherapy (45 Gy in 25 fractions), measured by 5-year relapse-free survival (RFS), over standard surgery in patients with high-risk lower rectal submucosal invasive cancer after local resection. The primary endpoint is 5 year RFS. The secondary endpoints are 10 years RFS, 5-year and 10-year overall survival, 5-year and 10-year local RFS, 5-year and 10-year proportion of anus-preservation without stoma, Wexner score, low anterior resection syndrome score, adverse events and serious adverse events. During the 5-year trial period, 210 patients will be accrued from 65 Japanese institutions.Ethics and dissemination The National Cancer Center Hospital East Certified Review Board approved this study protocol in October 2018. The study is conducted in accordance with the precepts established in the Declaration of Helsinki and Clinical Trials Act. Written informed consent will be obtained from all eligible patients prior to registration. The primary results of this study will be published in an English article. In addition, the main results will be published on the websites of Japan Clinical Oncology Group (www.jcog.jp) and jRCT (https://jrct.niph.go.jp/). As to data curation, it has not been prepared yet.Trial registration number jRCT1031180076